2022
DOI: 10.1002/nop2.1216
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ attitudes towards hospitalized older adults in a tertiary care setting in Ghana

Abstract: Introduction The increasing population of older adults and rapid increases in co‐morbidities globally has necessitated the need for a healthcare delivery system that meets the multifaceted needs of the growing population of older adults. Concurrent with these rising complex health needs is the importance of positive, non‐judgmental attitudes of health services providers towards older adults. Moreover, this is particularly important in the nursing profession, given nurses' significant and crucial roles in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The evidence suggests that despite a positive caring attitude of nurses towards hospitalised older adults in Ghana (Salia et al, 2022;Yakubu et al, 2022), many patients still experience compromised dignity during acute hospitalisation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence suggests that despite a positive caring attitude of nurses towards hospitalised older adults in Ghana (Salia et al, 2022;Yakubu et al, 2022), many patients still experience compromised dignity during acute hospitalisation .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that despite a positive caring attitude of nurses towards hospitalised older adults in Ghana (Salia et al, 2022; Yakubu et al, 2022), many patients still experience compromised dignity during acute hospitalisation (Fuseini, Rawson, et al, 2022). This can be attributed to several factors, including a lack of autonomy, inadequate privacy during care, ineffective HCP‐patient communication and a lack of involvement of family members in the physical aspects of care (Calnan et al, 2013; Tauber‐Gilmore, Addis, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing elderly population and the increase in diseases observed in old age reveal the importance of positive and nonjudgemental attitudes of healthcare professionals toward the elderly. 5 People who will work in this field need to know the theories and concepts about the ageing period, such as physiological and pathological changes of ageing, frailty and functionality in the elderly, and effective communication skills such as listening, respect and empathy. 6 It also reported that there is a lack of educators with gerontological knowledge, skills and necessary attitudes and there is need to investigate the factors affecting their attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The perceptions, attitudes and competence levels of health professionals who will work in these institutions and in health care services to be provided for the elderly are very important. The increasing elderly population and the increase in diseases observed in old age reveal the importance of positive and non‐judgemental attitudes of healthcare professionals toward the elderly 5 . People who will work in this field need to know the theories and concepts about the ageing period, such as physiological and pathological changes of ageing, frailty and functionality in the elderly, and effective communication skills such as listening, respect and empathy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been reported that ageism affects the well-being of the elderly negatively, causing depressive symptoms and low self-esteem (Marquet et al, 2019; Lyons et al, 2018). It is important to reduce ageism while older individuals receive health services in places such as hospitals and health care centers (Yakubu et al, 2022; Gholamzadeh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%